PROFIL DAN KOMPETENSI SARJANA AKUNTANSI - Widarno, Bambang (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
Abstract Accountant profession required by many corporate world. Competency had accountancy master very relevant with business growth in this time. And correction management company or organisation which business oriented and also public service require role of accountant, good that management accountant, public accountant, public sector accountant, and educator accountant. Only more plus accountancy master of competive in the world of job, that is master which can all knowledge, skilled, reflected attitude and value in habit of thinking and act. Plan with circumstantial analysis in chosening education institute in giving interest stock which is both for its grad represent step early facing to tighten emulation of job. Only our own which can change our future and chance Keywords: Competency, Master Of Accounting Plus, Profile Master of Accounting